Active and Passive Offline Breaks Differentially Impact the Consolidation of Procedural Motor Memories in Children and Adults - D. Voisin; P. Peigneux; C. Urbain (Brain and Behavior)
ABSTRACT Introduction Short post‐learning breaks, lasting from 5 to 30 min, transiently enhance procedural motor memory performance in adults. However, the impact of activity type (active vs. passive) during the offline break on sequential motor performance remains poorly investigated in children. Method This study examined the impact of active versus passive post‐learning breaks on procedural motor memory in 116 healthy participants (58 children, aged 9.03 ± 1.19; 58 adults, aged 22.89 ± 1.77 years). Participants practiced a Finger Tapping Task, reproducing a five‐element keypress sequence as fast and accurately as possible. The task included two sessions (S1 and S2) separated by either a short (30 min) or long (4 h) break. The first 30‐min of the post‐learning break included either a passive (remaining still) or an active (engaging in daily activities) condition. Results Repeated‐measures ANOVA revealed significant Session × Age group × Break duration and Session × Break type interaction effects (ps < 0.05). Post hoc analyses indicated Session effects in adults after both Break types, but only after short Break duration (S1 < S2, p < 0.001; long delay p = 0.1). In children, Session effects were observed after both short and long breaks, but only in the active Break type (S1 < S2, ps < 0.001; passive condition p = 0.1). Conclusion These results revealed spontaneous post‐learning motor performance improvements at both short and long delays in children, but only in the active post‐training condition, unlike adults who showed improvements only at short delays, regardless of activity type. This suggests developmental differences in offline conditions (duration and activity) linked to plasticity mechanisms underlying procedural motor memory consolidation.